A study of intervierwer's discourse used on "The Andrew Marr Show" and "Dân Hỏi Bộ Trưởng Trả Lời" - Lê Thị Ánh Tuyết (The University of Da Nang, 2014)
Introduction; Literature review and theoretical background; Methods and procedures; ...